2022
DOI: 10.3390/molecules27228028
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Assessment of Rhodanine-Linked Benzenesulfonamide Derivatives as Selective and Potent Human Carbonic Anhydrase Inhibitors

Abstract: A novel series of twenty-five rhodamine-linked benzenesulfonamide derivatives (7a–u and 9a–d) were synthesized and screened for their inhibitory action against four physiologically relevant human (h) carbonic anhydrase (CA) isoforms, namely hCA I, hCA II, hCA IX, and hCA XII. All the synthesized molecules showed good to excellent inhibition against all the tested isoforms in the nanomolar range due to the presence of the sulfonamide as a zinc binding group. The target compounds were developed from indol-3-ylch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Askin et al designed a protocol to synthesize new imidazole [2,1b] [1,3,4]thiadiazoles (73)(74)(75)(76)(77)(78)(79)(80)(81). Initially substituted benzyl chloride derivatives (62)(63)(64) were refluxed with KOH in presence of ethanol for 4-6 h to obtain 2-amino-1,3,4-thiadiazoles (66)(67)(68) Newly synthesized compounds were tested for their inhibitory activity against hCA I and hCA II by taking standard AAZ and THA and it was observed that compound 70b and 71 were found to be most potent against hCA I with K i values of 23.44 ± 4.92 and 51.53 ± 10.74 nM, respectively.…”
Section: S C H E M E 7 Synthesis Of 42(a-l)mentioning
confidence: 99%
See 1 more Smart Citation
“…Askin et al designed a protocol to synthesize new imidazole [2,1b] [1,3,4]thiadiazoles (73)(74)(75)(76)(77)(78)(79)(80)(81). Initially substituted benzyl chloride derivatives (62)(63)(64) were refluxed with KOH in presence of ethanol for 4-6 h to obtain 2-amino-1,3,4-thiadiazoles (66)(67)(68) Newly synthesized compounds were tested for their inhibitory activity against hCA I and hCA II by taking standard AAZ and THA and it was observed that compound 70b and 71 were found to be most potent against hCA I with K i values of 23.44 ± 4.92 and 51.53 ± 10.74 nM, respectively.…”
Section: S C H E M E 7 Synthesis Of 42(a-l)mentioning
confidence: 99%
“…proved to be best inhibitors of hCA XII with K i value of 9.0 nM as compared to AAZ (5.7 nM). SAR showed that both aryl and isatin derivatives with either electron donating or electron withdrawing group were showing good inhibitory activity [80] (Scheme 61). [81] (Scheme 62).…”
Section: S C H E M E 52 Synthesis Of 387(a-u)mentioning
confidence: 99%